Effect of TiO2Nanoliquid on the Properties of Cement Mortar - Prabalini, C; Aysha Farsana, Z; Sumathi, A (International Journal of Engineering and Technology, 2018)
Mortar/Concrete is effectively used in the construction of buildings. In the view of developing the infrastructure, it is essential to come up with new methods. Generally, the mortar which is being used has numerous pores in it and thus the strength gets reduced and the absorption increases. To reduce the durability problems nano liquid is being added. Nano liquid has the advantages of anti microbial and anti UV action. This paper deals with the nano liquid on the properties of cement mortar with two curing medium (water and saturated lime water) for 3, 7 and 28 days and the results were compared with control mortar in terms of strength and durability. Nano liquid was added in terms of 2.5ml, 5ml, and 7.5ml per kg of cement. After the completion of curing period the nano liquid is uniformly sprayed on the outer surface of the mortar cube. Since the nano liquid emits heat, the curing is made with lime to reduce the heat of hydration.Â Â